Green computing - Ng, Wing Lok. (2012)
Sustainability is a pressing issue with global warming and the depletion of natural resources threatening to disrupt our daily lives. The IT sector contributes to a significant proportion of energy consumption and the percentage will become bigger in the long run. The purpose of this project is to analyze which aspects of computing are going to be responsible for the growth in energy consumption and come up with solutions to mitigate the problem. An intensive review of related literature in the area of green computing was conducted and a lifecycle assessment model was used to determine the aspects that are likely to experience exponential growth and the potential in improving energy efficiencies in them. The results show that the manufacturing stage is responsible for most of the energy consumed in the lifetime of a computer, and various computer components such as the central processor appear to be approaching the physical limits from becoming more energy efficient. It is also noted that varying usage patterns results in significant differences in operational energy consumption and that e-waste is a worsening issue. Taking into consideration that computing has become highly integrated into our lives and that it would be impossible to expect a reduced usage, the design stage should now focus on software solutions to better utilize existing architectures while lengthening the lifespan of computers is the best answer to spreading out the manufacturing energy over a longer period and at the same time reducing e-waste in the disposal stage. In addition, user habits and awareness are the crucial factors towards lowering the energy consumed in the operational stage of computers as well as increasing the successfulness of e-waste disposal programs in the disposal stage.